Population Dynamics, Infectivity and Longevity of Anopheles Mosquitoes in Relation to Malaria Transmission in Bali District, Taraba State - Lamidi, Babatunde Tajudeen; Elijah, M. Iganga; Irebanije, J. Francis; Damburam, J. Hussaina; Dahiru, Faiza (Population Dynamics, Infectivity and Longevity of Anopheles Mosquitoes in Relation to Malaria Transmission in Bali District, Taraba State, 2022)
The community leaders of the study sites: Daniya Bali, Fundalara and Gazabubarkeji in Bali district of Bali Local Government of Taraba state were contacted and informed. Preliminary survey of the three villages was completed and verbal consent of the heads of households was sought before the commencement of the mosquito sampling last week of June 2018. Collection of mosquitoes by use of non-residual insecticide- pyrethrum (Spread Sheet Collection) was employed using World Health Organization (WHO) standard in the three riverine communities of Daniya Bali, Fundalara and Gazabubarkeji between June and December, 2018. The number of people that slept overnight in the room was noted. Collected and freshly preserved mosquitoes were sorted morphologically identified to species level. to species level. The ovaries of fed and unfed Anopheles gambiae were extracted and quickly transferred to drop of distilled water on the slide and examined under high magnificiation for tracheal skein and classified as parous or nulliparous. Human Blood Index (HBI) and Plasmodium sporozoite infection of the fed Anopheles gambiae was determined using biochemical method (ELISA). A total of 614 mosquitoes were morphologically identfied comprising of four species: Anopheles gambiae complex 589 (96.0%), Mansonia uniformis 11 (1.8%), Culex quinquefasciatus 12 (1.9%) and Aedes aegypti 2 (0.3%). Fundalara village had the highest mosquito population of 325 (52.9%), followed by Gazabubarkeji 194 (31.6%). The least was in Daniya Bali 95 (15.5%). ANOVA showed significant difference between mosquito abundance and study areas (P < 0.05). Prevalence of mosquito catch in seasons showed that there were more 509 (82.9%) than in dry season 105 (17.1%) Based on sex, female mosquitoes were more abundant 510 than the male 104 caught indoor. Among the 485 Anopheles gambiae, 191 were blood fed with HBI of 1 (100%) and Man-Biting Rate (MBR) 1.93 bite/man/night, sporozoite rate (SR) of 0.005 and Infective Biting Rate of 0.01. The SR and IBR were only recorded in wet season. Also the MBR during wet season 1.86 bite/man/night was more than that of dry season 0.07bite/man/night. T-test showed significant difference in mosquito abundance in seasons (P<0.05) but no statistical difference between MBR, SR and IBR in seasons (P>0.05). A total number of 485 adult female Anopheles gambiae mosquitoes were identified. The mosquitoes were higher in wet season 413 (85.2%) than dry season 72 (14.8%). Mosquito densities in relation to man were 4.13 and 0.81 during wet and dry seasons. Seasonal densities of the mosquitoes were significantly different (P<0.05). Proportion parous in wet season was 0.57 and dry season 0.47. The probabilities of daily survival of individuals of the mosquito, 0.75 and 0.688 during wet and dry seasons were not significantly different (P> 0.05). The life expectancy of adult mosquitoes was 8.0 days and 5.9days during wet and dry seasons and was significantly different (P < 0.05). The extrinsic incubation period of Plasmodium falciparum lasted for 10 days in wet season and 10.4days in dry season with no significant difference (P>0.05). During wet season the mosquitoes were more likely to survive long enough 0.06 to become infectious than during dry season 0.02. Thus the vectorial capacities of the mosquitoes, although low, was higher significantly 1.98 than that of the dry season 0.09 (P<0.05). The vectorial capacity of Anopheles gambiae for Plasmodium vivax was estimated to be a double of that for Plasmodium falciparum under similar ecological conditions. The implication of these findings is that the study area is prone to various mosquito-borne diseases especially malaria with possible higher transmission in wet season of the year. Also, the Anopheles gambiae population in Bali district was dominated by old mosquitoes due to high rates of daily survival. The longevity of this mosquito in this area with the favourable temperature for Plasmodium development, make for high vectorial potential to the transmission of malaria.